Reproducing the Shāfiʿī Intellectual Tradition: Knowledge Transmission and Religious Authority in Contemporary Indonesian Pesantren - Heni Noviarita; Rukmina Gonibal; Muhammad Saleh; Fauzan (KALAM, 2026)
The Shāfiʿī madhhab has long served as the dominant intellectual and legal tradition within Indonesian Islam, particularly through the educational system of pesantren. Despite extensive scholarship on pesantren and Islamic education, limited attention has been given to the mechanisms through which the Shāfiʿī tradition is transmitted and reproduced across generations. This study examines the processes of knowledge transmission and religious authority reproduction that sustain the continuity of the Shāfiʿī tradition in contemporary Indonesian pesantren. Employing a qualitative library research approach, the study analyzes classical Islamic texts and relevant scholarly literature using thematic content analysis, interpreted through Pierre Bourdieu’s theory of social reproduction. The findings reveal that the continuity of the Shāfiʿī tradition is maintained through three interconnected mechanisms: textual transmission, pedagogical transmission, and genealogical transmission through sanad networks. Religious authority is reproduced through the authority of kiai and the symbolic legitimacy embedded in sanad networks, while pesantren function as a reproductive religious field within which these processes take place. The study proposes a model of Shāfiʿī tradition reproduction in which cultural capital, symbolic capital, habitus, and religious authority interact to ensure the continuity of the tradition. This study contributes to discussions on Islamic education, religious authority, and the sociology of Islamic knowledge transmission. [Mazhab Syafi‘i telah lama menjadi tradisi intelektual dan hukum yang dominan dalam Islam Indonesia, terutama melalui sistem pendidikan pesantren. Meskipun kajian tentang pesantren dan pendidikan Islam telah berkembang luas, perhatian terhadap mekanisme yang memungkinkan tradisi Syafi‘i ditransmisikan dan direproduksi secara berkelanjutan masih relatif terbatas. Penelitian ini bertujuan menganalisis proses transmisi pengetahuan dan reproduksi otoritas keagamaan yang menopang keberlangsungan tradisi Syafi‘i di pesantren Indonesia kontemporer. Penelitian menggunakan pendekatan kualitatif berbasis studi kepustakaan dengan menganalisis teks-teks klasik Islam dan literatur akademik yang relevan melalui analisis tematik, yang kemudian diinterpretasikan menggunakan teori reproduksi sosial Pierre Bourdieu. Hasil penelitian menunjukkan bahwa keberlangsungan tradisi Syafi‘i dipelihara melalui tiga mekanisme yang saling terkait, yaitu transmisi tekstual, transmisi pedagogis, dan transmisi genealogis melalui jaringan sanad. Otoritas keagamaan direproduksi melalui otoritas kiai dan legitimasi simbolis yang tertanam dalam jaringan sanad, sementara pesantren berfungsi sebagai medan keagamaan reproduktif tempat proses-proses ini berlangsung. Penelitian ini menawarkan model reproduksi tradisi Syafi‘i yang menjelaskan interaksi antara modal kultural, modal simbolik, habitus, dan otoritas keagamaan dalam menjaga kontinuitas tradisi. Temuan ini berkontribusi pada pengembangan kajian pendidikan Islam, otoritas keagamaan, dan sosiologi transmisi pengetahuan Islam.]